Istanbul : The Monocle travel guide series (Berlin : Gestalten, 2015)
Beneath its inimitable skyline Istanbul is a teeming, triumphant metropolis with imperial history, intrigue and entrepreneurial zeal written into its streets. It's a city constantly being remade and reimagined, and the resulting sense of opportunity and vigour is palpable. We've sought out must)sees with an eye beyond the obvious, whether it's visiting the next up-and-coming neighbourhood ) brimming with bars, discerning clothiers and coffee houses - or dropping in to an old-school kuafor for a haircut. This guide will point you in the right direction for the finest places to eat, drink and shop, and navigate you through the city's architectural gems, from Ottoman follies converted into art centres to backstreet Byzantine beauties. So Join us for a cross-continental jaunt with bites of simit-sized lore thrown in for good measure. Now don't miss that ferry.
Keywords: Istanbul; Reisgids